Shared transcriptional regulators and network rewiring identify therapeutic targets linking type 2 diabetes mellitus and hypertension - Norzagaray-Valenzuela, Claudia Desireé; Valdez-Flores, Marco Antonio; Camberos-Barraza, Josue; De la Herrán-Arita, Alberto Kousuke; Osuna-Ramos, Juan Fidel; Magaña-Gómez, Javier; Angulo-Rojo, Carla; Guadrón-Llanos, Alma Marlene; Aviña-Padilla, Katia; Calderón-Zamora, Loranda (Frontiers in Molecular Biosciences, 2025)
BackgroundType 2 diabetes mellitus (T2DM) and Hypertension (HTN) frequently coexist and synergistically exacerbate vascular and immune dysfunction. Despite their clinical interrelation, these diseases have traditionally been studied in isolation, and the molecular mechanisms underlying their comorbidity remain poorly understood. This study aimed to uncover shared transcriptional programs and disease-specific regulatory networks contributing to cardiometabolic dysfunction.MethodsWe systematically selected transcriptomic datasets and employed an integrative systems biology approach that combined differential gene expression analysis, co-expression network construction, protein-protein interaction mapping, transcription factor activity inference, and network rewiring analysis. Functional enrichment analyses were conducted to elucidate biological processes associated with disease-specific modules.ResultsWe identified distinct regulatory modules: ME3 in T2DM, enriched in metabolic stress response, intracellular trafficking, and inflammation, and ME7 in HTN, enriched in immune response and vascular remodeling. Protein interaction networks revealed key hub genes such as GNB1, JAK1, and RPS3 as T2DM-specific hubs, while MAPK1, BUB1B, and RPS6 were central in HTN. Network rewiring analysis showed condition-specific changes in gene connectivity, particularly in ST18 and SLBP gaining prominence in T2DM, and SLC16A7 and SPX showing decreased connectivity in HTN. Notably, transcription factor activity analysis revealed shared regulators HNF4A and STAT2 implicated in inflammation, oxidative stress, and vascular remodeling, highlighting a transcriptional convergence between the two conditions.ConclusionThis study provides novel insights into the molecular crosstalk between T2DM and HTN by identifying conserved transcriptional regulators and rewired gene networks. Our findings support the existence of a shared regulatory architecture underlying cardiometabolic comorbidity and suggest promising diagnostic and therapeutic targets for precision medicine.